Effect of alloying additions and presence of water vapour on short-term air oxidation behaviour of cast Ni-base superalloys. (15th August 2020) - Wollgarten, K.; Galiullin, T.; Nowak, W.J.; Quadakkers, W.J.; Naumenko, D.
Graphical abstract: Highlights: 3% Al-addition to Ni-14Cr-9Co (wt.%) suppresses formation of Ni-rich oxides. Ti-addition to Ni-14Cr-9Co-3Al significantly increases chromia scale growth. 5wt.% Ta added to Ni-14Cr-9Co-3Al promotes alumina scale formation. Exposures in wet air increases growth of Ni-rich oxides compared to dry air. Abstract: Ni-14Cr-9Co (wt.%) based alloys with additions of Al, Ti and Ta were exposed in dry and wet (+20 vol.%H2 O) air at 950 °C for up to 100 h and characterized with GD-OES and SEM/EDX. Ni-14Cr-9Co-alloy exhibited initially Cr2 O3 -scale formation followed by breakaway Ni-oxidation. 3%Al addition to Ni-14Cr-9Co stabilized the Cr2 O3 -scale and largely suppressed Ni-oxide formation. Ni-14Cr-9Co-3Al-5Ti formed a fast growing Cr2 O3 -scale attributed to p-type Ti-doping, but Ni-oxide formation was completely inhibited. 5%Ta addition to Ni-14Cr-9Co-3Al promoted formation of a thin alumina scale. Addition of H2 O to the test gas increased growth of Ni-rich oxides and shortened time to breakaway for the Al-free alloy.